Caracterização microbiológica de água e peixes de área quilombola do município de Anajatuba, Maranhão: indicadores higiênico-sanitários, estirpes diarreiogênicas de Escherichia coli e genes enterotoxigênicos de estafilococos coagulase positiva - De Jesus, Greiciene Santos (2023)
The objective was to characterize the microbiological quality of fish and water in the quilombola area of the municipality of Anajatuba - MA, through the diagnosis of microorganisms that are hygienic-sanitary indicators and detection of diarrheagenic strains of Escherichia coli and enterotoxigenic genes of coagulase-positive staphylococci. For this, samples of water and fish were collected in a floodable environment, in two seasonal periods (dry and rainy), from the quilombola community of Ponta Bonita. Abiotic parameters (pH, dissolved oxygen, conductivity, temperature) were measured in situ and four samples of water from the flooded environment were collected. The captured fish specimens, 21 Hoplerythrinus unitaeniatus (jeju) and 21 Cichlasoma bimaculatum (black sugarfish) were transported alive in isothermal boxes in oxygenation to the State University of Maranhão. In a laboratory environment, the quantification of total coliforms and E. coli in water samples and complementary physical-chemical analyzes (alkalinity, chlorides, total dissolved solids, nitrate, nitrite, iron and turbidity) were carried out. After euthanasia of the fish, muscle fragments were collected and microbiological analyzes were carried out to characterize the microbiological quality of the collected fish: enumeration of molds and yeasts, strict and facultative aerobic mesophilic viable microorganisms and coagulase-positive Staphylococci (ECoP) , quantification of total and thermotolerant coliforms, E. coli and Salmonella sp. From the positive samples for E. coli and ECoP, the isolation and biochemical identification of the isolates were performed, followed by the extraction of DNA from the pure cultures and the characterization of the isolates by molecular analysis. The results of the study show that the water samples were altered in terms of physical (turbidity), chemical (OD, STD and iron) and microbiological (total coliforms and E. coli) parameters. As for the microbiological characterization of fish, 9.52% (n= 04/42) were considered unacceptable for human consumption for Salmonella. The enumeration of ECoP ranged from <10 to 3.9 x 104 ECoP/g, with 9.52% (n= 04/42) considered as an intermediate standard and 4.76% (n= 02/42) unacceptable for consumption. Of the total isolates, 33.34% (n=6/18) were coagulase positive staphylococci (ECoP) and 66.67% coagulase negative. Of the six ECoP isolates, three contained genes coding for the staphylococcal enterotoxins SEC and SEE, and a coagulase-negative staphylococcal isolate detected the gene SE that produces staphylococcal enterotoxin (SE). The quantification of E. coli ranged from 3.6 to >1,100 E. coli/g, with 4.76% (n= 02/42) considered an intermediate standard and 4.76% (n= 02/42) considered unacceptable for consumption. Forty bacterial isolates were obtained from fish and 20 from water samples that behaved as expected 9 for the standard E. coli species in the biochemical tests. With molecular analyses, virulence genes characteristic of the diarrheagenic pathotypes EPECa, EPECt and ETEC were identified in 10 isolates from water and in 30 isolates from fish, the pathotypes ETEC, EPECt and STEC. The quantification of total and thermotolerant coliforms and the enumeration of viable strict and facultative aerobic microorganisms and molds and yeasts revealed high bacterial populations, which suggests poor hygienic conditions at the capture site, contaminated raw material, in addition to the risk of the presence of fecal pathogens. Based on the results obtained, it is concluded that the microbiological characterization of H. unitaeniatus and C. bimaculatum showed microorganisms that are hygienic-sanitary indicators of Brazilian legislation, microorganisms that indicate useful storage time and microorganisms that indicate unsatisfactory hygienic conditions. The presence of these agents demonstrates imbalance in the studied environment. From the point of view of public health, an educational campaign aimed at quilombolas is important and necessary to raise awareness about good biosecurity practices, mainly related to the existence of other animals nearby, such as those raised for livestock purposes (pigs, cattle and buffaloes) and the need for periodic microbiological and physicalchemical monitoring of the flooding environment.